Fintech and Financial Inclusion in Latin America and the Caribbean - Gershenson, Dmitry; Herrera, Luis.; Lambert, Frederic; Ramos, Grey. (Washington, D.C. : International Monetary Fund, 2021)
Despite some improvement since 2011, Latin America and the Caribbean continue to lag behind other regions in terms of financial inclusion. There is no clear evidence that fintech developments have supported greater financial inclusion in LAC, contrary to what has been observed elsewhere in the world. Case studies by national policy experts suggest that barriers to entry in the financial sector, along with a constraining regulatory environment, may have hindered a faster adoption of fintech. However, fintech development seems to have accelerated in the wake of the COVID-19 pandemic and with the support of recent policy initiatives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economywide Country Studies; Financial Institutions and Services; Financial Markets and the Macroeconomy; Monetary Systems